Computationally derived RNA polymerase III promoters enable maize genome editing - Nagy, Ervin D.; Davis, Ian W.; Song, Shanshan; No, Valerie; Wu, Chenxi; Kanizay, Lisa; Turner-Hissong, Sarah; Li, Hong; Ye, Xudong; Berry, Jeffrey C.; Chiapelli, Brandi; To, Jennifer P. C.; et al. (Frontiers in Plant Science, 2025)
CRISPR endonucleases require cognate non-coding RNA species for site-specific activity. These RNA species are typically expressed using endogenous RNA polymerase III (Pol III) promoters compatible with the host species. This study describes applications of novel Pol III promoters, which were computationally derived from a training set of monocot U6 and U3 promoters. These promoters enabled genome editing in maize protoplast cells and maize plants. Out of 37 novel promoters, 27 performed similarly to a control U6 promoter. Multiplexing five novel promoters in one construct enabled simultaneous editing of the maize genome at 27 unique sites in a single plant. Moreover, repeating the same CRISPR RNA (crRNA) with multiple novel promoters improved editing up to three-fold at a low-efficiency target site in maize plants. The ability to computationally derive novel Pol III promoters on-demand increases genome editing flexibility and efficiency in maize.